Skema Ponzi: Indikasi Kecurangan Pada Valuasi Startup Menggunakan Gross Merchandise Value - Prayuda, Jun Rifky; Zakiyuddin, Zakiyuddin; Firmansyah, Amrie (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Startup-related issues have been growing in recent years due to their massive publication in the media. The growth numbers of startup companies globally, especially in Indonesia, have shown an astonishing figure. Valuation is one of many issues that revolve around startups. This study examines valuation fraud that leads to Ponzi Scheme in startup companies by using Gross Merchandise Value (GMV) as the valuation indicator. Scoping review was employed to identify and map literature that links to this study’s topic comprehensively through many sources. Venture capitalists and management teams play a key role in valuing startups. Financial academics suggest general valuation models, such as Net Present Value (NPV) and Discounted Cash Flows (DCF), are not used to value startups. They tend to value their company subjectively, which doesn’t represent startup true economic values. They use their advantages on information asymmetry excessively, leading to overvaluing the startup’s values. This study concludes that using subjective factors and limiting a startup’s economic and performance information disclosure by only disclosing Gross Merchandise Value will lead to startup valuation fraud in the form of the Ponzi Scheme.